1998
DOI: 10.1007/s004210050408
|View full text |Cite
|
Sign up to set email alerts
|

Systemic oxygen extraction during incremental exercise in patients with severe chronic obstructive pulmonary disease

Abstract: To determine if decreased systemic oxygen (O2) extraction contributes to the exercise limit in severe chronic obstructive pulmonary disease (COPD), 40 consecutive incremental cycle ergometer exercise tests performed by such patients, from which a "log-log" lactate threshold (LT) was identified, were compared to those of 8 patients with left ventricular failure (LVF) and 10 normal controls. Pulmonary gas exchange and minute ventilation were measured continuously and arterial blood gas tensions, pH, and lactate … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
8
0

Year Published

2000
2000
2015
2015

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 17 publications
(9 citation statements)
references
References 44 publications
1
8
0
Order By: Relevance
“…Similarities in cardiovascular responses to exercise in COPD and mitral stenosis were reported by Venami et al [40]who found similar decreases in right ventricular ejection fraction. At the anaerobic threshold, Nery et al [47]reported that oxygen uptake in mitral stenosis was decreased, as it is in COPD [30, 48, 49]. These findings are consistent with a low anaerobic threshold in both CHF and COPD due to right ventricular dysfunction, leading to relative ischemia of exercising muscles.…”
Section: Cardiovascular Factors Limiting Exercise In Copdsupporting
confidence: 77%
See 2 more Smart Citations
“…Similarities in cardiovascular responses to exercise in COPD and mitral stenosis were reported by Venami et al [40]who found similar decreases in right ventricular ejection fraction. At the anaerobic threshold, Nery et al [47]reported that oxygen uptake in mitral stenosis was decreased, as it is in COPD [30, 48, 49]. These findings are consistent with a low anaerobic threshold in both CHF and COPD due to right ventricular dysfunction, leading to relative ischemia of exercising muscles.…”
Section: Cardiovascular Factors Limiting Exercise In Copdsupporting
confidence: 77%
“…For an anaerobic threshold which occurs at a V̇ O2 of 1,500 ml O 2 /min, the oxygen cost of breathing would be about 150 ml O 2 /min. Contrast this situation with a patient with COPD having a V̇ O2 max of only 1,000 ml/min with an anaerobic threshold at 30% V̇ O2 max [49]or only 300 ml/min just slightly above the total body O 2 requirements at rest. Such a patient would have very little opportunity to exercise aerobically.…”
Section: The Competition Between Ventilatory and Skeletal Musclesmentioning
confidence: 97%
See 1 more Smart Citation
“…The results of blood gas analysis and oximetry both at rest and on exercise, plus BMI measures confirmed this. The potential contributions of drug therapy and cigarette smoking to skeletal muscle dysfunction have been mentioned recently by OELBERG et al [19]. These factors would not explain the current results.…”
Section: Discussionmentioning
confidence: 54%
“…In a previous study, maximal oxygen consumption in stroke patients during incremental exercise was lower than that in healthy subjects [7]. A decrease in respiratory function causes a rapid increase in the blood lactate concentration even at a low work rate; i.e., a decrease in LT [25].…”
Section: Discussionmentioning
confidence: 78%